High frequency of methicillin-susceptible and methicillin-resistant Staphylococcus aureus in children under 1 year old with skin and soft tissue infections - Lorena Salazar-Ospina; Judy Natalia Jiménez (Elsevier, 2018)
Objective: Staphylococcus aureus is responsible for a large number of infections in pediatric population; however, information about the behavior of such infections in this population is limited. The aim of the study was to describe the clinical, epidemiological, and molecular characteristics of infections caused by methicillin-susceptible and resistant S. aureus (MSSA-MRSA) in a pediatric population. Method: A cross-sectional descriptive study in patients from birth to 14 years of age from three high-complexity institutions was conducted (2008-2010). All patients infected with methicillin-resistant S. aureus and a representative sample of patients infected with methicillin-susceptible S. aureus were included. Clinical and epidemiological information was obtained from medical records and molecular characterization included spa typing, pulsed-field gel electrophoresis (PFGE), and multilocus sequence typing (MLST). In addition, staphylococcal cassette chromosome mec (SCCmec) and virulence factor genes were detected. Results: A total of 182 patients, 65 with methicillin-susceptible S. aureus infections and 117 with methicillin-resistant S. aureus infections, were included in the study; 41.4% of the patients being under 1 year. The most frequent infections were of the skin and soft tissues. Backgrounds such as having stayed in day care centers and previous use of antibiotics were more common in patients with methicillin-resistant S. aureus infections (p ≤ 0.05). Sixteen clonal complexes were identified and methicillin-susceptible S. aureus strains were more diverse. The most common cassette was staphylococcal cassette chromosomemec IVc (70.8%), which was linked to Panton-Valentine leukocidin (pvl). Conclusions: In contrast with other locations, a prevalence of infections in children under 1 year of age in the city could be observed; this emphasizes the importance of epidemiological knowledge at the local level. Resumo: Objetivo: O Staphylococcus aureus é responsável por um grande número de infecções na população pediátrica; contudo, as informações sobre o comportamento dessas infecções nessa população são limitadas. O objetivo do estudo foi descrever as características clínicas, epidemiológicas e moleculares de infecções causadas por Staphylococcus aureus suscetíveis e resistentes à meticilina (MSSA-MSRA) em uma população pediátrica. Método: Um estudo transversal descritivo foi realizado em pacientes entre 0 e 14 anos de idade de três instituições de alta complexidade (2008-2010). Todos os pacientes infectados com S. aureus resistentes à meticilina e uma amostra representativa de pacientes infectados com S. aureus suscetíveis à meticilina foram incluídos. As informações clínicas e epidemiológicas foram obtidas de prontuários médicos, e a caracterização molecular incluiu tipagem spa, Eletroforese em Gel de Campo Pulsado (PFGE) e Tipagem de sequências multilocus (MLST). Além disso, o Cassete Cromossômico Estafilocócico mec (SCCmec) e genes de fatores de virulência foram detectados. Resultados: 182 pacientes, 65 com infecções por S. aureus suscetíveis à meticilina e 117 com infecções por S. aureus resistentes à meticilina, foram incluídos no estudo; 41,4% dos pacientes com menos de um ano de idade. As infecções mais frequentes foram da pele e dos tecidos moles. Os históricos como internações em centros de atendimento e o uso prévio de antibióticos foram mais comuns em pacientes com infecções por S. aureus resistentes à meticilina (p ≤ 0,05). Dezesseis complexos clonais foram identificados, e as cepas de S. aureus suscetíveis à meticilina foram mais diversificadas. O cassete mais comum foi o Cassete Cromossômico Estafilocócicomec IVc (70,8%), relacionado à leucocidina de panton-valentine (pvl). Conclusões: Em comparação a outros locais, observamos uma prevalência de infecções em crianças com menos de um ano de idade na cidade; o que enfatiza a importância de conhecer a epidemiologia em nível local. Keywords: Staphylococcus aureus, MSSA, MRSA, Pediatric, Epidemiology, Molecular biology, Palavras-chave: Staphylococcus aureus, MSSA, MRSA, Pediatria, Epidemiologia, Biologia molecular